(untitled) (Applied Biological Research, 2022)
An attempt was made to standardize in vitro clonal propagation of pomegranate cv. Bhagwa, using nodal segment and shoot tip explants at e, India. Direct organogenesis of pomegranate was tried in MS medium with growth regulator combinations viz., benzyl amino purine (BAP), α-naphthalene acetic acid (NAA) and adenine sulphate for in vitro shoot regeneration and indole butyric acid (IBA) for in vitro rooting. Among the explants evaluated, nodal segments responded better for culture establishment. Pre-treatment of nodal segments with 0.5% carbendazim for 30 min followed by surface sterilization with 70% ethanol for 30 sec and 0.5% sodium hypochlorite for 10 min gave highest survival rate (81.7%) with minimum microbial contamination (13.3%). Phenolic exudation was reduced by treating explants in antioxidant solution consisting of citric acid (100 mg L-1) and ascorbic acid (150 mg L-1) for 20 min and then cultured on basal MS medium with polyvinyl pyrrolidone (100 mg L-1) resulted in maximum survival (98.3%). The earliest shoot evocation response (4.4 days), higher shoot proliferation (91.7%) and maximum shoot number (4.6) were observed on basal MS medium with adenine sulphate (40 mg L1). Half strength MS medium supplemented with IBA (1 mg L-1), recorded minimum days to root initiation (16.9) and maximum rooting percentage (71.7%) with highernumber of roots explant-1(3.7) and lengthier roots (3.93 cm). Rooted plantlets transferred to hardening media with pot mixture and vermicompost (1:1) exhibited an ex-vitro survival of 81.7%.